Serum carboxyl-terminal propeptide of procollagen type I in exercise-induced left ventricular hypertrophy - Escudero, Eduardo Manuel (2004)
Background: Left ventricular hypertrophy (LVH) induced by exercise is considered to be a physiologic adaptive mechanism without fibrogenic hyperactivity, as occurs in pathologic hypertrophy. Hypothesis: This study investigated serum markers of collagen synthesis and echo parameters of left ventricular diastolic function (LVdf) in 22 male athletes. Methods: Twenty-two highly competitive male athletes (10 cyclists, 12 soccer players) were studied with full history, clinical examination, Doppler echocardiogram, and serum concentration of the carboxyl-terminal propeptide of collagen type I (PIP). They were divided into two groups: normal left ventricular mass (N) with left ventricular mass index (LVMI) < 125 g/m2 (14 athletes) and LVH with LVMI > 125 g/m2 (8 athletes). Results: Age, body surface area, blood pressure, heart rate, and systolic function were not different between the groups. Serum concentration of PIP (N: 163 ± 44.1 µg/l, LVH: 172.7 ± 61.2 µg/l—NS) and LVdf (early to atrial peak mitral flow velocity ratio: [E/A] N:1.77 ± 0.47, LVH: 1.98 ± 0.70—NS, and early to atrial peak mitral annulus velocity ratio: [Ea/Aa] N: 2.63 ± 0.70, LVMI: 2.55 ± 0.90 LV1.61—NS) were similar in both groups. Conclusions: Normal serum concentration of PIP in athletes with LVH in association with normal LVdf indicates the possibility that in this type of physiologic hypertrophy there is mainly an increase of myocyte size without interstitial fibrosis.